The Effect of Plyometric Training Methods on Athlete Smash Ability Volleyball for Physical Education Students at Insan Budi Utomo University Malang - Riska Yunanda Putra; Winarno Winarno; Ahmad Junaidi; Alfian Yahyar; Yuskhil Mushofi (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
Study This aim for now influence method plyometric training against athlete's smash ability volleyball college high. The research method used is experiment with pre-test post-test design. Research sample consists of 20 athletes’ volleyball student. The Department of Physical Education and Health Recreation was given a 6-week plyometric training program. Instrument study in the form of test measured smash ability through accuracy and power blow. The results of the data analysis show existence improvement significant on the group's smash ability experiment compared to group control. Plyometric training is proven effective increase Power explosion muscle legs and coordination movement, so that impact positive to smash quality. Conclusion from study This is method plyometric exercises can made into alternative training strategies for increase performance athlete volleyball, in particular in smash skills.